Libraries: a year of crisis. And transformation? - Selgas, Joaquín (Anuario ThinkEPI, 2011)
This review of major developments in the library world in 2010 analyzes the impact of the global economic crisis through budget cuts to library services, with some examples from the Anglo-Saxon world in contrast to the Spanish case, and its adverse impact on the supply of services, collections and investments. On the contrary, we see continued and rising demand, mainly focused on collections and digital based services. The digitization of collections and the incorporation of electronic books are consolidated as the central elements of the operation and services of all types of libraries.